The Argumentation in Governments’ Public Crisis Communication: A Case of a NIMBY Facility in City Z of Mainland China (Sinología hispánica. China Studies Review, 2016)
Argumentativeness is an attribute not to beneglected in the crisis communication discourse.This paper constructs an argumentation-orientedpublic crisis communication model. The newmodel incorporates the well-established rulesand two-way symmetric principle in crisiscommunication with argumentation analysisand evaluation under the theory of pragmadialectics.By analyzing the strategies andevaluating the effects of a local Chinesegovernment’s crisis communication related witha proposed NIMBY facility in Mainland China, thecase is employed to underline the significanceof the new model in real crisis communication.